2016
DOI: 10.1021/acsami.6b00853
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Cell Membrane Camouflaged Au Nanoshells for in Vivo Prolonged Circulation Life and Enhanced Cancer Photothermal Therapy

Abstract: Macrophage cell membrane (MPCM)-camouflaged gold nanoshells (AuNS) that can serve as a new generation of photothermal conversion agents for in vivo photothermal cancer therapy are presented. They are constructed by the fusion of biocompatible AuNSs and MPCM vesicles. The resulting MPCM-coated AuNSs exhibited good colloidal stability and kept the original near-infrared (NIR) adsorption of AuNSs. Because AuNS carried high-density coverage of MPCMs, the totally functional portions of macrophage cells membrane wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
217
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(223 citation statements)
references
References 44 publications
0
217
0
Order By: Relevance
“…38 In recent years, it has been shown that leukocytes are effective in carrying drugs and nanoparticles for cancer therapy, 39,40 while leukocyte cell membrane-camouflaged nanoparticles preserve the surface properties of parent leukocytes and provide a platform for biomimetic delivery. 22,[41][42][43] ICAM-1 is a ligand for LFA-1, which is found on vascular endothelium, squamous cell …”
Section: Discussionmentioning
confidence: 99%
“…38 In recent years, it has been shown that leukocytes are effective in carrying drugs and nanoparticles for cancer therapy, 39,40 while leukocyte cell membrane-camouflaged nanoparticles preserve the surface properties of parent leukocytes and provide a platform for biomimetic delivery. 22,[41][42][43] ICAM-1 is a ligand for LFA-1, which is found on vascular endothelium, squamous cell …”
Section: Discussionmentioning
confidence: 99%
“…The MPCM-coated AuNS were applied for photothermal cancer therapy. Upon laser irradiation, local heat generated by the MPCM-coated AuNS achieved sufficiently high efficiency to suppress tumor growth and selectively ablated cancerous cells [140]. …”
Section: Nanomedicines Targeting Dysfunctional Macrophage-associatmentioning
confidence: 99%
“…[438] In fact, derived and purified cellular membrane from a cell source is integrated with the surface of nanoparticles to somehow "camouflage" them. Several reports have proved significant MPS evasion and tumor accumulation of nanoparticles through coating them with the membranes of erythrocytes, [439] leukocytes, [440] platelets, [441] and macrophage cells [442] as well as "self" peptides such CD47. [443] A simple sonication method can be applied to fully coat nanoparticles by exploiting the asymmetric charge of the cell membranes.…”
Section: Wwwadvancedsciencenewscom Wwwadvhealthmatdementioning
confidence: 99%